Late-Onset Crohn's Disease Is A Subgroup Distinct in Genetic and Behavioral Risk Factors With UC-Like Characteristics. Issue 11 (30th May 2018) - Li, Dalin; Haritunians, Talin; Landers, Carol; Potdar, Alka A; Yang, Shaohong; Huang, Hailiang; Schumm, L Philip; Daly, Mark; Targan, Stephan R; McGovern, Dermot P B
Abstract: Background: Age of onset is linked to variations in clinical phenotypes and natural history in Crohn's disease (CD). We aim to define etiologically more homogenous subgroups in CD based on ages of onset. Methods: We examined the distribution of CD polygenetic risk score (PRS) across ages of diagnosis in a Caucasian cohort of 2344 independent CD patients. We identified subgroups with a distinct distribution of PRS and compared those groups in genetics, demographic characteristics, clinical subphenotypes, and serological markers. The results were replicated in an independent cohort of 13, 065 CD patients from the International Inflammatory Bowel Diseases Genetic Consortium (IIBDGC). Results: We identified a late-onset (LO) subgroup in CD (age at diagnosis ≥ 55 years) with significantly lower PRS compared with the intermediate group (age at diagnosis between 5 and 55 years) in both cohorts. Smoking cessation, a risk factor for ulcerative colitis (UC) and protective factor for CD, had a higher rate in this LO subgroup in comparison with the intermediate group. We also compared the LO group with the intermediate group, and, consistent with previous reports, the LO group more often had colonic CD, had less penetrating disease behavior, and had less need for surgery. Serological analysis showed that LO CD patients were more antineutrophil cytoplasmic antibody positive and less antisaccharomyces cerevisiae antibody positive compared with the intermediate group. Variance component analysis indicated that overall genetic contribution to LO CD was lower relative to the middle group, and genetic heterogeneity testing indicated that LO CD was different from the middle group in underlying genetic architecture. Conclusions: Late-onset CD is subgroup distinct in genetic and behavioral risk factors with UC-like characteristics.